Mechanical and microstructural characterization of epoxy/sawdust (Pinus elliottii) composites - Mendes, Caroliny P (2020)
The use of wood residues in polymeric matrices is notable for promoting significant mechanical reinforcement of the matrix. Such composites are widely used in the development of new composite materials with tunable mechanical properties for a variety of applications. In this work, polymeric composites with epoxy resin as the polymeric matrix and Pinus elliottii wood residue as the reinforcement were obtained. The composites were obtained by adding wood residue (sawdust) with particle sizes of 0.30, 0.60, and 1.19 millimeters into an epoxy matrix to determine the best mechanical properties of the composite as a function of the particle size. The polymer/sawdust composites were characterized by scanning electron microscopy (SEM), Infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and stress–strain tests. SEM images revealed a smooth and homogeneous surface free of defects and holes. However, lateral profile images showed the presence of fine sawdust particles agglomerated and a considerable number of bubbles and cavities that could interfere in the mechanical properties of the composites. The FTIR characterization of the composite identified the main bands related to epoxy and lignin/cellulose chains. The results of the mechanical properties suggested that epoxy composites with sawdust can increase its tensile strength according to the sawdust particle size introduced into the matrix.